2021
DOI: 10.1093/cz/zoab029
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming induced a stretch of the breeding season and an increase of second clutches in a passerine breeding at its altitudinal limits

Abstract: The increase in the average air temperature due to global warming has produced an early onset of the reproduction in many migratory birds of the Paleartic region. According to the ‘mismatch hypothesis’ this response can lead to a decrease in the breeding output when the conditions that trigger the departure from the wintering areas do not match the availability of food resources in the breeding ground. We used 653 brooding events registered during the period 1991-2013 to investigate the link between climatic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…2022) and longer seasons (alpine population of the Rock Sparrow Petronia petronia ; Mingozzi et al . 2021), whereas others show lower fledging success in years with an early onset of breeding (Snow Bunting Plectrophenax nivalis ; Fossøy et al . 2015), or the fitness advantage of early breeding has been reduced over time (Wheatear; Arlt & Pärt 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2022) and longer seasons (alpine population of the Rock Sparrow Petronia petronia ; Mingozzi et al . 2021), whereas others show lower fledging success in years with an early onset of breeding (Snow Bunting Plectrophenax nivalis ; Fossøy et al . 2015), or the fitness advantage of early breeding has been reduced over time (Wheatear; Arlt & Pärt 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Clutches experiencing a rainy season or severe weather events, such as snow storms, have a prolonged incubation period, exposing the nest to predators for a longer period at the same time, and generally higher failure rates (due to abandonment, hatch failure and predation) than clutches in a dry season (Rauter et al, 2002;Kluen et al, 2011;Higgot et al, 2020;Marcelino et al, 2020). Further explanations for variations in breeding success in alpine birds include annual variations in temperature, where success is lower in years with lower mean temperatures (Mingozzi et al, 2021), but also variations in weather-dependent resources (Barras et al, 2021) and local predation risk (Rauter et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1, population A), is characterized by a level of EPP (around 50% of the broods contain extra-pair offspring; Pilastro et al 2002, Nemeth et al 2012, which is among the highest reported for passerines (Brouwer and Griffith 2019). The location of this population in the range limit of the species distribution (Mingozzi et al 2021) may support the hypothesis that the high level of EPP may occur to compensate reductions in the population's genetic diversity expected in marginal populations (Eckert et al 2008). To answer this question, we estimated the rate of EPP in a rock sparrow population located in the core of its distribution range (central Spain, Fig.…”
Section: Introductionmentioning
confidence: 91%